Chemical reactor analysis and applications for the practicing engineer - Theodore, Louis (Wiley, 2012)
"This books format follows an applications-oriented text and serves as a training tool for individuals in education and industry involved directly, or indirectly, with chemical reactors. It addresses both technical and calculational problems in this field. While this text can be complimented with texts on chemical kinetics and/or reactor design, it also stands alone as a self-teaching aid. The first part serves as an introduction to the subject title and contains chapters dealing with history, process variables, basic operations, kinetic principles, and conversion variables. The second part of the book addresses traditional reactor analysis; chapter topics include batch, CSTRs, tubular flow reactors, plus a comparison of these classes of reactors. Part 3 keys on reactor applications that include non-ideal reactors: thermal effects, interpretation of kinetic data, and reactor design. The book concludes with other reactor topics; chapter titles include catalysis, catalytic reactors, other reactions and reactors, and ABET-related topics. An extensive Appendix is also included"--